BML-111 Reduces Neuroinflammation and Cognitive Impairment in Mice With Sepsis via the SIRT1/NF-κB Signaling Pathway - Shangwen Pan; Yan Wu; Lei Pei; Shengnan Li; Limin Song; Haifa Xia; Yaxin Wang; Yuan Yu; Xiaobo Yang; Huaqing Shu; Jiancheng Zhang; Shiying Yuan; et al. (Frontiers in Cellular Neuroscience, 2018)
Sepsis is a life-threatening state of organ dysfunction caused by infection and which can induce severe neurological disorders that lead to neuroinflammation and cognitive impairment. Inflammation has been reported to cause neuronal apoptosis in sepsis, which can finally lead to cognitive impairment. Previous studies have suggested that BML-111 can exhibit anti-inflammatory and proresolution activities. Additionally, silent information regulator 1 (SIRT1) can inhibit the NF-κB signaling pathway in an inflammation state. However, the role of the SIRT1/NF-κB signaling pathway in the protective effects of BML-111 against sepsis-induced neuroinflammation and cognitive impairment remains unclear. This study aimed to determine the effects of BML-111 on neuroinflammation and cognitive impairment induced by sepsis. Male C57BL/6J mice were subjected to cecal ligation and puncture (CLP) or a sham operation. BML-111 was administered via intracerebroventricular injection (0.1 mg/kg) immediately after CLP. Boc-2 (50 μg/kg) was administered intracerebroventricularly 30 min before CLP, and EX527 (10 μg) was administered every 2 days for a total of three times before CLP, also intracerebroventricularly. Some of the surviving mice underwent open-field, novel-object-recognition, and fear-conditioning behavioral tests at 7 days after surgery. Some of the other surviving mice were killed at 24 h after surgery to assess synaptic damage (PSD95 and Synapsin1), markers of inflammation [tumor necrosis factor alpha (TNF-α) and interleukin (IL)-1β], cytoplasmic p65, nuclear p65, Ac- NF-κB and SIRT1. At 48 h after CLP, TUNEL and glia-activation by immunofluorescence investigations were performed on a separate cohort of surviving animals. The results suggested that sepsis resulted in cognitive impairment, which was accompanied by the decreased the expression of PSD95 and Synapsin1, increased amount of TUNEL-positive cells and the activation of glias, increased production of TNF-α and IL-1β, increased expression of nuclear p65, Ac- NF-κB, and decreased expression of SIRT1 and cytoplasmic p65. It is especially notable that these abnormalities could be reduced by BML-111 treatment. EX527, an SIRT1 inhibitor, abolished the effects of BML-111. These results demonstrate that BML-111 can reduce the neuroinflammation and cognitive impairment induced by sepsis via SIRT/NF-κB signaling pathway.